Penggunaan Diksi dan Gaya Bahasa dalam Novel Segi Tiga Karya Sapardi Djoko Damono - Asriana, Desi; Sukenti, Desi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This research is motivated by the importance of using diction and language style in novels. Through this study of diction and language style, it is hoped that there will be an understanding of critically studying literary works and creating a broad understanding to search for meaning in actual literary works. The problems in this research are: 1) How is diction used in the novel Segi Tiga by Sapardi Djoko Damono? 2) How is language style used in the novel Segi Tiga by Sapardi Djoko Damono? The aim of this research is to find out, describe, analyze and interpret the use of diction and language style in the novel Segi Tiga by Sapardi Djoko Damono. The theory used in this research is the theory of Gorys Keraf (2010), as well as other supporting theories. This research data consists of all data, phrases, clauses, sentences and paragraphs in the novel Segi Tiga by Sapardi Djoko Damono which contains diction and language style. This research uses a content analysis method with this type of research using a qualitative approach. The data collection technique uses hermeneutic techniques and is analyzed using content analysis techniques. This research shows that there is use of diction and language style in the novel Segi Tiga by Sapardi Djoko Damono. Synonymous diction was found totaling 27 data, antonymy totaling 42 data. Meanwhile, the language style of equations or similes is 16 data, metaphor is 2 data, personification is 71 data, and irony is 4 data. Thus, the results in this research that have the most dominant data in the novel Segi Tiga by Sapardi Djoko Damono are the personification language style.